Wadi Khashab : unearthing late prehistory in the Eastern Desert of Egypt - Osypiński, Piotr (Polish Publications in Mediterranean Archaeology, 2021)
The 5th millennium BC megalithic ceremonial complex at Wadi Khashab in the Eastern Desert of Egypt is located almost directly in the middle of the Eastern Desert, on a wadi trail connecting the Valley of the Nile with the Red Sea. The volume presents the results of three seasons of excavation of this site, which featured a human burial in the center of several burials of cattle and sheep, within an enclosure of upright stone slabs that must have formed an eye-catching landmark for many miles up and down the wadi, also for the pastoral communities traversing the mountains in later times. The study of the animal remains from this remote site in the poorly known Eastern Desert has provided a very well documented series of osteological, osteometric and archaeozoological data on early cattle and sheep. It adds to the current knowledge of cattle domestication in the Neolithic and early cattle mobility in northeastern Africa, offering unique information on the uses of domestic livestock not only in the funerary traditions, but also in mobility systems. It also contributes to the discussion on the origins and domestication of the auroch in Africa, pointing to a local African origin for the cattle.